Supply chain strategy and the role of suppliers: evidence from the Indian sub-continent. Issue 7 (3rd October 2016) - Jajja, Muhammad Shakeel Sadiq; Kannan, Vijay R.; Brah, Shaukat Ali; Hassan, Syed Zahoor
Abstract : Purpose: Supply chain strategy is widely recognized as being a crucial component of a broader corporate strategy. However, the relationships between a firm's strategic supply chain focus, the tactical orientation of its suppliers, and the firm's performance, are less well understood. Much of what is known is also based on developed country contexts. The purpose of this paper is to empirically examine relationships between a buying firm's supply chain strategy and operational dimensions of its suppliers in a developing country context. Design/methodology/approach: A structural equation model is developed and tested using empirical data drawn from 296 organizations in India and Pakistan. Findings: The results demonstrate a positive relationship between a firm's strategic supply chain focus (lean and responsiveness) and key supplier practices (quality, cost effectiveness, delivery, and flexibility), which in turn have a positive impact on firm performance (operational, quality and market, and financial). Practical implications: The study paper offers supply chain managers in developing markets with insights that can shape effective supplier selection and management and lead to positive performance outcomes. Originality/value: The results provide insights into supply chain strategy, and empirically validate the importance of the alignment between strategy and the ability of suppliers to execute in a corresponding manner. It also offers evidence of the impact of the buyer-supplier interface in a developing market context.